Auditing Banks: relationship between issues cited in modified opinion, emphasis and KAM - Santana, Lucas Rodrigues (2019)
The purpose of this study was to verify the relationship between the topics cited as a basis for modified opinion, emphasis paragraphs and the key audit matters (KAM) in the audit work carried out in Brazilian banks. Using the content analysis technique, the reports issued by the auditors on the statements of 134 Brazilian banking institutions, from 2007 to 2016, were examined, totaling 746 reports. The results of the examinations revealed that the topics related to deferred tax assets, provisions and actuarial passive issues are directly associated among those used as basis for modified opinion, emphasis paragraph and KAM. Operational continuity is prominent for both modified opinion and emphasis, but not as KAM. Asymmetric behavior is highlighted in the most cited issues for modified opinion (leasing) and KAM (provision for losses on credit operations), which have little relevance in the other topics. The research contributes to the development of the national literature on auditing, insofar as it assesses the association between the issues that have received more attention of the independent auditors in the preparation of their reports on the Brazilian banks' statements, whether as a modification of opinion, emphasis or KAM – an approach not yet explored in the literature on the subject.